Electroacupuncture treatment ameliorates depressive-like behavior and cognitive dysfunction via CB1R dependent mitochondria biogenesis after experimental global cerebral ischemic stroke - Hu, Guangtao; Zhou, Cuihong; Wang, Jin; Ma, Xinxu; Ma, Hongzhe; Yu, Huan; Peng, Zhengwu; Huang, Jing; Cai, Min (Frontiers in Cellular Neuroscience, 2023)
Introduction This study aimed to identify the effect of electroacupuncture (EA) treatment on post-stroke depression (PSD) and explore whether cannabinoid receptor 1 (CB1R)-mediated mitochondrial biogenesis accounts for the treatment effect of EA. Methods The PSD mouse model was induced by a consecutive 14-day chronic unpredictable stress operation after 7 days of recovery from the bilateral common carotid artery occlusion surgery. Either EA treatment or sham stimulation was performed for 14 consecutive days from Day 7 after the BCCAO operation. Subjects’ PSD-like behaviors were tested via open field test, sucrose preference test, novelty suppressed feeding test, tail suspension test, and forced swim test, and subjects’ cognitive function was examined using Y-maze and novelty object recognition test. In addition, the levels of CB1R, mitochondrial biogenesis-related proteins (nuclear transcription factor 1, NRF1; mitochondrial transcription factor A, TFAM), proteins related to mitochondrial function (Cytochrome C, Cyto C; AIF, COX IV), and mitochondrial DNA were measured. To elucidate the role of CB1R in EA treatment, CB1R antagonists AM251 and CB1R-shRNA were given to mice before EA treatment. Likewise, subjects’ depressive-like behaviors, cognitive function, mitochondrial function, and mitochondrial biogenesis were examined after the PSD procedure. Results It has been showed that EA successfully ameliorated depressive-like behaviors, improved cognitive dysfunctions, and upregulated CB1R, NRF1 and TFAM expressions. However, the supplementation of AM251 and CB1R-shRNA blocked the antidepressant-like effects generated by EA, and EA failed to improve cognitive dysfunction, upregulate CB1R protein expression, and increase mitochondrial function and biogenesis. Conclusion Altogether, these results indicated that EA ameliorated PSD-like behaviors in mice, improved cognitive dysfunctions after PSD, and promoted mitochondrial biogenesis by activating CB1R, a novel mechanism underlying EA’s antidepressant-like effects in treating PSD.